Fluid Flow and Entropy Generation Analysis of Al2O3–Water Nanofluid in Microchannel Plate Fin Heat Sinks - Hao Ma; Zhipeng Duan; Liangbin Su; Xiaoru Ning; Jiao Bai; Xianghui Lv (Entropy, 2019)
The flow in channels of microdevices is usually in the developing regime. Three-dimensional laminar flow characteristics of a nanofluid in microchannel plate fin heat sinks are investigated numerically in this paper. Deionized water and Al2O3−water nanofluid are employed as the cooling fluid in our work. The effects of the Reynolds number (100 < Re < 1000), channel aspect ratio (0 < ε < 1), and nanoparticle volume fraction (0.5% < Φ < 5%) on pressure drop and entropy generation in microchannel plate fin heat sinks are examined in detail. Herein, the general expression of the entropy generation rate considering entrance effects is developed. The results revealed that the frictional entropy generation and pressure drop increase as nanoparticle volume fraction and Reynolds number increase, while decrease as the channel aspect ratio increases. When the nanoparticle volume fraction increases from 0 to 3% at Re = 500, the pressure drop of microchannel plate fin heat sinks with ε = 0.5 increases by 9%. It is demonstrated that the effect of the entrance region is crucial for evaluating the performance of microchannel plate fin heat sinks. The study may shed some light on the design and optimization of microchannel heat sinks.